Anti-proliferative bacteriocin active against MRSA from coagulase negative Ent. mundtdii strain C4L10 isolated from non broiler chicken - Tengku Abdul Hamid, Tengku Haziyamin; Alhaji Yusuf, Moshood; Arief Ichwan, Solachuddin Jauhari (Journal of Probiotics & Health, 2014)
Bacteriocins produced by a variety of microbes are gaining more attention for not only as alternative foodpreservative but also as therapeutics agent. A bacteriocin, Ent C4L10, was produced by coagulase negative Enterococcus mundtii strain C4L10 (Accession No. KC731423) previously isolated from Malaysian non-broiler chicken. Based on agar diffusion assay, it showed antimicrobial activities against Methicillin resistance Staphylococcus aureus (MRSA) used as an indicator organism. Approximately 10 kDa protein was purified employing three-phase partitioning (TPP) method and it was shown to be highly thermostable, retaining activities at 121°C for 15 min, and was stable in a pH range of 4-9. There was however a loss in activity after protease treatment. PCR amplification using enterocin gene primers showed that Ent C4L10 sequence is highly similar to bacteriocinL-1077 (83% identity). In order to study its anti-proliferative potential, purified Ent C4L10 was also tested against four human cell lines; i.e., lung cancer (H1299), breast cancer (MCF 7), colon cancer (HCT116) and oral cancer (HSC3). It was found that oral cancer cell line wasthe most sensitive with a cytotoxic index of IC50 of 9.009 µg/ml, followed by breast cancer IC50 (11.51 µg/ml), and the least sensitive was with colon cancer cell line (IC50 of 20.57 µg/ml). In conclusion, putative 10KDaEnt C4L10 is a class II bacteriocin isolated from coagulase negative Enterococcus mundtii strain C4L10 shown to have anti-proliferative properties. Therefore, this bacteriocin has not only great potential for use in food preservation, its future use as an antitumoragent should also be explored.